Study of power and voltage delivery after successfully black-start - Andika Pradnya Satriawan; Saidah Saidah; Taufik Taufik (SINERGI, 2022)
Efforts to maintain the continuity of electricity distribution to customers and reduce the amount of Energy Not Distributed (END) are to speed up the recovery process due to disturbances in the electricity distribution system, especially blackouts. The strategy to speed up recovery in a total blackout is to do a black-start on a generator unit with a black-start facility and send voltage to a larger generator unit. At the Grati-Paiton Substation, the generator that has black-start facilities is the Grati Gas Steam Power Plant (GSPP). The delivery of power and voltage from the Grati-Paiton substation is required after the Grati GSPP successfully black-start. Study optimal power flow simulation in distributing power and voltage using DigSILENT software. Based on the simulation results, several schemes are used to distribute power and voltage from the Grati-Paiton substation within the generator’s Mvar. As a result, the voltage during the distribution process meets the criteria according to the Grid. The most optimal scheme is with the least number of stages, the production of Mvar, which is still safe for power generation, and the voltage at the end of the Paiton substation still meets the nominal voltage according to the Grid.